The Importance of Local Sustainable Food Systems in Ensuring Food Security - Eman, Katja (11. Nacionalna konferenca o varnosti v lokalnih skupnostih: Odpornost lokalnih skupnosti na varnostna tveganja, 2025)
The European Union introduced a rural development policy for the period 2023–2027 under the second pillar of the Common Agricultural Policy in 2023. It is intended to support rural areas in the European Union in addressing the economic, environmental, climate, and social challenges of the 21st century. Member States have written down rural development measures in the form of national strategic plans, which are divided into four strands: 1) Promoting the competitiveness of agriculture, food and forestry; 2) Caring for the environment and adapting to climate change; 3) Balanced development of rural areas; and 4) Transfer of knowledge and innovation. The key objective of the policy is to improve the quality of life and strengthen economic activity in rural areas. The author analyses the priorities of agricultural policy for rural development and, through the prism of rural criminology, discusses increasing competitiveness, ensuring sustainable management of natural resources and climate change measures, and achieving balanced territorial development of rural economies and communities, highlighting advantages and disadvantages.